The comparative study of capsicum anthracnose pathogens from Korea with that of China - SHIN Hyun-joo; XU Tong; ZHANG Chu-long; CHEN Zhu-jun (浙江大学学报. 农业与生命科学版, 2000)
Anthracnose of capsicum casued by Colletotrichum spp. (C. spp.) has been a great problems for capsicum production in Korea and China. Based on morphological characters, the capsicum anthracnose pathogen isolates K1 and Cl, K2 and C2, K3 and C3 were identified as Colletotrichum gloeosporioides G type, C. gloeosporioides R type and C. coccodes, respectively. Pathogenicity of Korea isolate and China isolate in capsicum lines of Korea and China did not show a difference. Results of RAPD-PCR analyses indicate that the similarities between Kl and Cl. K2 and C2, and K3 and C3 were 85.71%, 71.43% and 50.0%, respectively.